Hortensia Maggi's Natalia Mértens (1996): take up the Torch and pronounce the Verb (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
Hortensia Maggi's figure is set around two variables that crossed both its public participation as their written: being female and member of the Socialist Party. She publishes Natalia Mertens in 1996; a novel with autobiographical traits in which a framework of values and ideological concepts that overlap the fictional plot with political militancy of the author works. The protagonist of the novel is outlined as a subject who is aware of the marginal status of women and social injustice. This characterization is linked to the particularities acquires omniscient narrator's voice in this novel. The analysis allows to read filiation and affiliations, in terms of Edward Said (2004), which are configured in this novel.
Keywords: Hortensia Maggi; socialist women; fiction